2015
DOI: 10.1096/fj.15-274761
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node biophysical remodeling is associated with melanoma lymphatic drainage

Abstract: Tissue remodeling is a characteristic of many solid tumor malignancies including melanoma. By virtue of tumor lymphatic transport, remodeling pathways active within the local tumor microenvironment have the potential to be operational within lymph nodes (LNs) draining the tumor interstitium. Here, we show that lymphatic drainage from murine B16 melanomas in syngeneic, immune-competent C57Bl/6 mice is associated with LN enlargement as well as nonuniform increases in bulk tissue elasticity and viscoelasticity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 86 publications
(114 reference statements)
6
45
0
Order By: Relevance
“…For example, sentinel, or tumor-draining, lymph nodes are exposed to a high concentration of lymph-transported molecules from the tumor interstitium by virtue of their proximity to growing tumors (Figure 1) (7, 8). Signaling pathways active within the local tumor microenvironment that result in tissue remodeling associated with cancer cell survival (44), invasion (4547), and immune suppression (5) could therefore operate within tumor-draining lymph nodes.…”
Section: Lymphatic Transport–directed Remodeling Of the Lymph Nodementioning
confidence: 99%
See 3 more Smart Citations
“…For example, sentinel, or tumor-draining, lymph nodes are exposed to a high concentration of lymph-transported molecules from the tumor interstitium by virtue of their proximity to growing tumors (Figure 1) (7, 8). Signaling pathways active within the local tumor microenvironment that result in tissue remodeling associated with cancer cell survival (44), invasion (4547), and immune suppression (5) could therefore operate within tumor-draining lymph nodes.…”
Section: Lymphatic Transport–directed Remodeling Of the Lymph Nodementioning
confidence: 99%
“…Signaling pathways active within the local tumor microenvironment that result in tissue remodeling associated with cancer cell survival (44), invasion (4547), and immune suppression (5) could therefore operate within tumor-draining lymph nodes. We recently analyzed lymph nodes from B16 melanoma–bearing mice with respect to tumor stage and found that melanoma lymphatic drainage was associated with alterations in lymph node hyaluronic acid and collagen content corresponding with physical adaptations that manifest in tumors (44, 48, 49), including increased intranodal pressures (7, 50, 51) and increased lymph node tissue stiffness and viscoelasticity (7). The potential for these and other remodeling responses to influence critical cellular processes in the lymph node, including cell proliferation, migration, and lymphocyte homing, is discussed below.…”
Section: Lymphatic Transport–directed Remodeling Of the Lymph Nodementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, tumor-draining lymph nodes often display altered immunological microenvironments relative to non-tumor associated lymph nodes, suggesting active regulation of the tumor-draining lymph node microenvironment by the tumor to suppress anti-tumor immunity. We and others have noted lymph node remodeling associated with tumor lymphatic drainage [17,18,8385], effects that may alter antigen, cytokine, growth factor, or even therapeutic agent accumulation within and distribution throughout tumor-draining lymph nodes to alter their signaling activity [18]. Furthermore, increased frequencies of regulatory T cells [86] and low densities of CD169 + subcapsular sinus macrophages [87] within tumor-draining lymph nodes predicts poor patient outcome in melanoma [86].…”
Section: Opportunities and Potential Strategies For Improving Checmentioning
confidence: 99%